Serratus anterior plane block for acute pain management after pectus excavatum repair - Rim, Gongmin; Park, Hyung Joo; Kang, Seungyoun; Jeong, Jin Yong; Koo, Jungmin; Jang, Il-Tae; Bae, Saemi (Frontiers in Surgery, 2024)
Introduction: Conventional postoperative pain management using an intravenous (IV) patientcontrolled approach or thoracic epidural analgesia is suboptimal following minimally invasive repair of the pectus excavatum (MIRPE). Recently, cryoanalgesia has gained popularity owing to its superior pain control outcomes compared to those associated with conventional methods. However, because of its invasiveness, additional instrumentation requirement, and limited effect at early postoperative periods, we hypothesized that serratus anterior plane block (SAPB) could be an effective method for post-repair pain management and a possibly superior alternative.We conducted a retrospective cohort study of pediatric patients who had undergone MIRPE between March 2022 and August 2023. We compared the efficacy of pain control in three groups among 74 patients: Group N (conventional pain management, n=24), Group C (cryoanalgesia, n=24), and Group S (SAPB, n=26). Group N received IV patient-controlled analgesia (PCA) and a subcutaneous local anesthetic infusion. Group C received bilateral cryoanalgesia on the fourth and seventh intercostal nerves using a cryoprobe at -80°C for 2 min during the operation and IV-PCA postoperatively. Group S received continuous bilateral SAPB with 0.75% ropivacaine and IV-PCA.The pain levels were measured using the visual analog scale (VAS; resting and dynamic), and the total IV rescue analgesic consumption was determined.The three groups had similar baseline characteristics. Group S showed significantly less pain throughout the immediate postoperative course, resting VAS score at 3 h (Group N, 7.21 vs. Group C, 5.75 vs. Group S, 3.81; p<0.001), and prominent less total IV rescue analgesic consumption (Group N, 116.16 mg vs. Group C, 52.75 mg vs. Group S, 16.61 mg; p<0.001).Conclusion: SAPB resulted in better postoperative pain control than that associated with cryoanalgesia and conventional pain management after pectus excavatum repair, As it was effective in the immediate postoperative period, achieving a VAS score of <4 points (moderate pain) at 3 h postoperatively, it may play an important role and replace invasive cryoanalgesia in the management of pain after pectus surgery.